Resilience Analysis of Energy Sources in the Cuban Economy in Years 1971-2050: Empirical Herfindahl-Hirschman and Lauraeus-Kaivo-oja Index Analyses / Análisis de la resiliencia de las fuentes energéticas en la economía Cubana entren los anôs 1971-2050: Análisis empíricos utilizando los índices Herfindahl-Hirschman y Lauraeus-Kaivo-oja - Kaivo-oja Jari; Luukkanen Jyrki; Vehmas Jarmo (Cuba, 2025)
This paper focuses on the Cuban economy and its resiliency of energy sources. This study includes three analyses of resilience, (1) total energy consumption, (2) indigenous energy sources, and (3) import energy consumption. These three resilience analyses are performed with Herfindahl-Hirschman Index and Lauraéus-Kaivo-oja Index. The time horizon of the resilience analyses is 1971-2018. In addition to these historical energy sources analyses also a long-run IEA scenario till the year 2050 for Cuba will be operationalised with HHI and LKI analyses. These resilience analyses of the Cuban energy economy provide useful insights into the Cuban energy planning processes.
Programa General y Técnico: CONVENCIÓN CIENTÍFICA DE INGENIERÍA Y ARQUITECTURA DE LA CUJAE, 20 CCIA 2022